(untitled) (Third Sector Social Economic Review, 2022)
The aim of the study is to ensure that the brand heritage; its effects on brand awareness, brand attitude, brand trust, and purchase intention; it is to determine whether the brand heritage attitude differs according to gender, age groups, and educational status. A conceptual model was developed within the scope of the research goals. This study sets itself apart from similar papers in this stream of research since it aims to explore the effect of brand heritage on brand awareness and attitude. An extensive literature review was carried out, and it was observed that no such model had been tested before. Most previous studies attempted to determine the effect of brand heritage on consumers’ purchase intentions and brand trust, directly or indirectly. Additionally, a limited number of studies investigated whether brand heritage attitude differs according to specific demographic factors such as a consumer’s age, gender, and educational level. Along similar lines, it is noteworthy that it is the first study carried out with the brands covering various areas of the food industry. In order to determine the sample of the research, the easily accessible (easily) sampling method was chosen among the improbable sampling methods, and the data were obtained as a result of the online questionnaire applied to 720 people. The collected data were analyzed using SPSS 25.0 statistical program, and hypotheses were tested with regression analysis. As a result of the research, it was found that brand heritage has a positive effect on brand awareness, brand attitude, brand trust, and purchase intention; It has been determined that the brand heritage attitude differs according to age.